Viral Evasion of the Complement System and Its Importance for Vaccines and Therapeutics - Mellors, Jack; Tipton, Tom; Longet, Stephanie; Carroll, Miles (Frontiers in Immunology, 2020)
The complement system is a key component of innate immunity which readily responds to invading microorganisms. Activation of the complement system typically occurs via three main pathways and can induce various antimicrobial effects, including: neutralisation of pathogens, regulation of inflammatory responses, promotion of chemotaxis, and enhancement of the adaptive immune response. These can be vital host responses to protect against acute, chronic, and recurrent viral infections. Consequently, many viruses (including dengue virus, West Nile virus and Nipah virus) have evolved mechanisms for evasion or dysregulation of the complement system to enhance viral infectivity and even exacerbate disease symptoms. The complement system has multifaceted roles in both innate and adaptive immunity, with both intracellular and extracellular functions, that can be relevant to all stages of viral infection. A better understanding of this virus-host interplay and its contribution to pathogenesis has previously led to: the identification of genetic factors which influence viral infection and disease outcome, the development of novel antivirals, and the production of safer, more effective vaccines. This review will discuss the antiviral effects of the complement system against numerous viruses, the mechanisms employed by these viruses to then evade or manipulate this system, and how these interactions have informed vaccine/therapeutic development. Where relevant, conflicting findings and current research gaps are highlighted to aid future developments in virology and immunology, with potential applications to the current COVID-19 pandemic.